PERANCANGAN APLIKASI PENGOLAHAN NILAI IJAZAH MENGGUNAKAN BAHASA PEMROGRAMAN VB.NET DAN DATABASE MYSQL - Nofriadi man; Elma wati; Ayunismar Ayunismar (Sekolah Tinggi Teknologi Industri Padang, 2022)
The processing students’ test scores which is a part of teaching and learning activities. The assessment system is implemented as a benchmark of the students’ success in learning process and the results of their competencies in certain subjects. The design of this School Diploma Value Processing Application is expected to help the school in processing students’ scores and avoid the occurrence of repeated input of same data which takes a long time. This application design uses a system development method, that is the System Development Life Cycle (SDLC) with Visual Basic.Net programming language and MySQL database which is a software of Database Management System (DBMS). This application design presents reports in the form of student data, subject data, Graduation Certificate, Certificate of Examination Results and Collection of Students’ Report Grades. The Certificate of Graduation and the Certificate of Examination Results are temporary, but they can be used by the students as conditions for continuing to a higher level education before the original certificate is handed over to the students.